Mothers in Law: Towards Equality within the Profession for Lawyer Mothers - Jaremko Bromwich, Rebecca; McElroy, Anne-Marie; Chang Knapton, Juliet Lucy (Journal of the Motherhood Initiative for Research and Community Involvement, 2021)
Mothers who work in the legal profession face a wide range of obstacles to their success. This article reports on a qualitative study of lawyer-mothers in Ottawa, Ontario, that problematizes and calls into question the widely held assumption that the law profession is on a path of progress towards better accommodation for the needs of mothers, thereby troubling assumptions that gender equality in the legal profession is generally improving.